Soroprevalência da infecção pelo virus da Hepatite C e dos fatores de risco para aquisição de hepatites virais em cirurgiões-dentistas de Belo Horizonte - Vera Lúcia Silva Resende (2007)
During the last decades, some reports have alerted dentists and other dental workers to the potential risk of infection with bloodborne pathogens while providing patient care. Studies conducted before hepatitis B vaccine bacame available indicated that dentists and oral surgeoon had a higher prevalence of hepatitis B virus (HBV) infection than other health care workers and a severalfold heger prevalence than the general population. In 1989 hepatitis C virus (HCV), was discribed. As chronic hepatitis C virus HCV infection is mostly asymptomatic, most often cases are discovered by chance due to the necessity of blood tests, or when the disease is in a advanced stage. Anti-HCV test is recommended for persons who have been injected illegal drugs, received plasma-derived products known to transmit HCV infection that were not treated to inactivate viruses, received blood transfusions or solid organ transplants before 1992, were ever on chronic hemodialysis, or have evidence of liver disease,health care professionals, and children born from HCV-positive.The objective of this study was to evaluate the seroprevalence of antibodies against Hepatitis C virus (anti-HCV), and to investigate the prevalence of some risk factors to other viral hepatitis among dentists. The calculated sample comprised 1302 individuals, out of 6973 dentists registered at the Dental Council of the state of Minas Gerais/Brazil, who lived or worked in the city of Belo Horizonte. A pre-tested questionnaire was used to assess the risk factors for viral hepatitis, and EIA-ELISA III to determine the seroprevalence of anti HCV. Results showed that the prevalence of anti-HCV positive was 0.9% and that the prevalence of accidents with needlesticks, considered to be the most important factor risk to hepatitis C virus transmission, was 85%. Results also showed that 74% of the dentists had been vaccinated against hepatitis B (3 doses scheme). In conclusion, the seroprevalence of antiHCV was low, nevertheless prevalence of accidents with sharps was high, and was not influenced by gender, work time or work place.